Pengaruh Zakat Terhadap Kinerja Bank Syariah Indonesia - Siregar, Erry Zulkifly; Nasution, Yenni Samri Juliati (Medan Resource Center, 2025)
This study examines the impact of zakat distribution on the performance of Bank Syariah Indonesia during the 2019–2023 period. Zakat distribution is a critical component in strengthening the Islamic economic framework, especially within Islamic banking as a prominent financial institution. The study employs simple linear regression analysis using SPSS 25 to evaluate the relationship between zakat distribution and financial performance indicators, including profitability, operational efficiency, and financial stability. The results demonstrate that zakat distribution significantly enhances the financial performance of Bank Syariah Indonesia. Specifically, an increase in zakat distribution positively correlates with improved operational efficiency and profitability, showcasing effective management of zakat funds in bolstering the bank's activities. The study concludes that optimizing zakat management can be a pivotal strategy for enhancing the competitiveness and sustainability of Bank Syariah Indonesia amidst evolving economic conditions.